2001
DOI: 10.1097/00001648-200107000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Recall Bias in a Case-Control Surveillance System on the Use of Medicine during Pregnancy

Abstract: It is important to study possible teratogenic effects of drugs used during pregnancy. Many studies of this type rely upon case-control designs in which drug intake is recalled by the mothers after having given birth. Recall bias in this situation may lead to spurious associations. We looked for indicators of recall bias by comparing self-reported drug intake with medically notified intake for specific diseases in the Hungarian Case-Control Surveillance System of Congenital Abnormalities, which includes 22,865 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 24 publications
2
116
1
Order By: Relevance
“…Reporting inaccuracy was minimized by using indication-based prompts for medication use 38 -43 ; furthermore, recall of medications is likely to be relatively accurate for prescription medications taken in early pregnancy for chronic hypertension. 41 Because infants without malformations served as controls, recall bias is a concern; however, we think differential recall among case mothers compared with control mothers is not a likely explanation for our findings, because we observed associations for some CVM groups and not others and for some classes of antihypertensive medications and not others. The meticulous case review decreased the misclassification of the cases and heterogeneity of the case groups 28,30 ; however, the sample sizes for the analyses of specific CVMs in relation to antihypertensive medication use were small, leading to imprecise estimates.…”
Section: Hypothesis Generationmentioning
confidence: 68%
“…Reporting inaccuracy was minimized by using indication-based prompts for medication use 38 -43 ; furthermore, recall of medications is likely to be relatively accurate for prescription medications taken in early pregnancy for chronic hypertension. 41 Because infants without malformations served as controls, recall bias is a concern; however, we think differential recall among case mothers compared with control mothers is not a likely explanation for our findings, because we observed associations for some CVM groups and not others and for some classes of antihypertensive medications and not others. The meticulous case review decreased the misclassification of the cases and heterogeneity of the case groups 28,30 ; however, the sample sizes for the analyses of specific CVMs in relation to antihypertensive medication use were small, leading to imprecise estimates.…”
Section: Hypothesis Generationmentioning
confidence: 68%
“…Recall error and biased OR up to a factor of 1.9 in casecontrol studies on maternal medication during pregnancy have been shown [42]. As infections are suspected as a cause of cancer at least in leukemia since a long time, parents of children with cancer may recall the event better, whereas parents of controls may simply not remember or may believe an exposure to be unimportant and underreport it [43].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, DNA specimens were not collected from either mothers or children to evaluate genotype. Vitamin use could also be a surrogate marker for other factors that may be associated with childhood leukemia, 30 including health behaviors that may not have been addressed adequately in our analysis. However, because we observed a protective overall effect for ALL and not AML, it seems unlikely that residual confounding explains these results.…”
Section: Discussionmentioning
confidence: 99%